Forms of Complicity in the Structures of Domination - Jaworski, Hélan (1971)
In this paper, the author examines the forms of complicity that are created in the structures of domination, as well as the way in which these forms can be used to maintain power. In that sense, the article argues that society is complicit and collaborates with the structures of domination and dependence that persist in the American continent. In that context, from the author’s perspective, oppression and dependence should not be studied as abstract events, but as concrete concepts that directly affect society. Due to this, the article teaches us that complicity is a dynamic and difficult to understand manifestation. Thus, to overcome the structures of oppression and achieve human liberation, it requires, in addition to a collective action, a critical reflection of this phenomenon.